National audit of the management of peritonsillar abscess - Mehanna, H (BMJ Group, 2002)
An anonymous postal survey of 200 consultants was used to audit the current prevalent practices in the management of quinsy in the UK; 101 responded. The findings reveal that on average an otolaryngology department treats 29 cases per year, the vast majority (94%) on an inpatient basis. The main initial treatment was needle aspiration combined with intravenous antibiotics. Interestingly, those departments treating more than 20 cases a year are more likely to use needle aspiration, while departments in England and Wales use significantly more incision and drainage than those in Scotland. Incision and drainage (52%) was the most common form of treatment of non-resolving patients. The median hospital stay was two days.